Islamic Social Reporting and Financial Distress In List of Sharia Securities - Cahyani, Utari Evy; Ardiansyah, Misnen; Sunaryati, Sunaryati (Ekonomi Syariah IAIN Kudus, 2020)
The number of sharia-approved companies in the Indonesia Stock Exchange is growing rapidly. It is important to see how the social performance of these companies, using Islamic Social Reporting Index (ISR Index). Financial Distress as an early sign of a company’s failure is also important to study. This study examines the relation between ISR Index and financial distress in list of sharia securities. The control variables apply in this research are SIZE, ROA, CR, WCTR, DER, and RETA. By using a sample of 129 companies from financial statements and annual reports (2014-2018), three models were built with the Modified Altmans Z-Score, Ohlson O-Score and Zmijewski Zm-Score as a proxy of financial distress. Based on ISR index calculation, the theme of products and services has the highest disclosure score. The lowest disclosure score is corporate governance theme. Panel data regression results show that ISR Index affects financial distress in the Modified Altman’s model. It means the higher the ISR index value, the greater the likelihood of companies run into financial distress. Whereas in Ohlson’s and Zmijewski’s model, ISR Index has no effect on financial distress.